2018
DOI: 10.1177/1367493518807312
|View full text |Cite
|
Sign up to set email alerts
|

Documentation of breakthrough pain in narrative clinical records of children with life-limiting conditions: Feasibility of a retrospective review

Abstract: This study explored the feasibility of generating reliable information on the frequency, nature and management of breakthrough pain (BTP) in children with life-limiting conditions and life-threatening illnesses (LTIs) from narrative clinical records. In the absence of standardized ways for documenting BTP, we conducted a consensus exercise to develop a glossary of terms that could denote BTP in the records. Thirteen clinicians who contributed to the records reached consensus on 45 terms which could denote BTP,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(31 citation statements)
references
References 48 publications
(73 reference statements)
2
29
0
Order By: Relevance
“…That is comparable to the reported prevalence of BTP pain in adults with chronic non-cancer pain 5 7. Similarly, BTP is common in children with cancer or life-limiting conditions (LLCs),8 9 including those with communication and/or learning difficulties as well as pre-verbal infants, for which assessment of BTP is a particular challenge. The single small study investigating BTP in a population of children with LLCs10 showed that 57% out of 27 hospitalised children with cancer who had controlled background pain reported having experienced BTP in the previous 24 hours.…”
Section: Introductionsupporting
confidence: 55%
See 2 more Smart Citations
“…That is comparable to the reported prevalence of BTP pain in adults with chronic non-cancer pain 5 7. Similarly, BTP is common in children with cancer or life-limiting conditions (LLCs),8 9 including those with communication and/or learning difficulties as well as pre-verbal infants, for which assessment of BTP is a particular challenge. The single small study investigating BTP in a population of children with LLCs10 showed that 57% out of 27 hospitalised children with cancer who had controlled background pain reported having experienced BTP in the previous 24 hours.…”
Section: Introductionsupporting
confidence: 55%
“…The single small study investigating BTP in a population of children with LLCs10 showed that 57% out of 27 hospitalised children with cancer who had controlled background pain reported having experienced BTP in the previous 24 hours. A retrospective review of clinical records showed that younger children (aged 7–12 years) had a significantly higher risk of BTP compared with teenagers and children and that children can experience BTP even when following a pain management strategy to control background pain 9…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subjective reporting of feeding and feelings of nausea from notes had to be relied upon, as well as parental/carer/patient reporting of number, volume and intensity of vomiting. 32 Subjective self or proxy reporting of efficacy may have also contributed to conformation bias, with those evaluating interventions at the time seeking to correlate the intervention with a positive rather than negative outcome. 33 In addition, lack of repeated probing and questioning around adverse effects, may have contributed to attribution of symptomology associated with disease progression to the disease rather than to the addition of aprepitant.…”
Section: Discussionmentioning
confidence: 99%
“…ICYP’s palliative care needs often differ from those of adults, and the diversity of conditions in this population means that practitioners must manage a wide range of complex symptoms 3. A particular challenge is managing continuous ‘background’ pain as well as bouts of severe, sudden-onset ‘breakthrough pain’, both of which are common in ICYP with a terminal illness4 and are known to be underassessed and undertreated 5…”
Section: Introductionmentioning
confidence: 99%